A comparative study on decolorization of AB172 and BR46 textile dyes by electrochemical processes: multivariate experimental design - Ilhan, Hilal; Can, Orhan Taner; Guvenc, Senem Yazici; Can-Guven, Emine; Varank, Gamze (WILEY, 2025)
BACKGROUND Textile dyes, used for coloring fabrics, cause environmental challenges because approximately 30% of the applied dye may enter the wastewater without being treated. This wastewater has intense color, variable pH, and salt content. Limited biodegradability of dyes due to their complex polymer structures necessitates advanced treatment. This study investigated the decolorization of dyeing wastewater by electrocoagulation (EC) and electrooxidation (EO) methods, which are common techniques of electrochemical advanced oxidation processes. Box-Behnken design was applied to experimental design in the determination of the maximum removal efficiency. Initial pH, current density (CD), and reaction time (RT) were chosen as independent variables, and the removal efficiency of Acid Black 172 (AB172) and Basic Red 46 (BR46) dyestuffs was selected as model responses.RESULTS Higher BR46 dyestuff removal efficiency was obtained by the EO process using a Ti:RuO2:IrO2 electrode, and higher AB172 dyestuff removal efficiency was obtained by the EC process using an Al electrode. Under optimum conditions, the highest removal efficiencies based on dyestuff were 93.4% with the EC process for AB172 dyestuff (initial pH 5.63; CD 0.07 mA cm-2; RT 13.1 min) and 94.0% for BR46 dyestuff with the EO process (initial pH 4.61; CD 2.89 mA cm-2; RT 72.6 min).CONCLUSION The study suggests that electrochemical methods hold promise for treating dyeing wastewater, providing water recovery and appropriate modeling. Both EC and EO processes, when optimized via Box-Behnken design, offer high dye removal efficiencies with low energy requirements, highlighting their suitability for sustainable textile wastewater treatment. (c) 2025 Society of Chemical Industry (SCI).
Keywords: Box-Behnken design; electrocoagulation; electrooxidation; process optimization; textile dyes; RESPONSE-SURFACE METHODOLOGY; SYNTHETIC ORGANIC-DYES; WASTE-WATER; REMOVAL; OPTIMIZATION; OXIDATION; WASTEWATERS; DECONTAMINATION; DEGRADATION; Biotechnology & Applied Microbiology; Chemistry; Engineering